Analisis Fuel Ratio Pada Project Penambangan di Pit 1 PT Cahaya Riau Mandiri Jobsite PT Duta Alam Sumatera - Yunita Yunita; Edwin Harsiga (MINERAL, 2023)
This study analyzed the fuel ratio in mining projects to determine the factors that affected loose opportunity and the profit or losses encountered by the company. This analysis process was conduted by determining the target and realization of production where the overburden and coal getting production target in March on Fleet 1 was 68.885 bcm/month with the fuel consumption of 11.907,19 liter, on Fleet 2 was 70.944 tons/month with the fuel consumption of 11.460,38 liter, on Fleet 3 was 68.885 bcm/month with the fuel consumption of 9.611,94 liter, Fleet 4 was 68.885 bcm/month with the fuel consumption of 11.907,19 liter. Whereas, in the field the realization of overburden and coal getting production in march of Fleet 1 was 55.403,23 bcm/month, Fleet 2 was 51.907,52 tons/month, Fleet 3 was 18.259,34 bcm/month, Fleet 4 was 56.582,92 bcm/month. The planned fuel ratio on Fleet 1 was 0,17 liter/bcm, Fleet 2 was 0,16 liter/tons, Fleet 3 was 0,14 liter/bcm and Fleet 4 was 0,17 liter/bcm while the actual fuel ratio on Fleet 1 was 0,18 liter/bcm, Fleet 2 was 0,20 liter/tons, Fleet 3 was 0,16 liter/bcm, Fleet 4 was 0,18 liter/bcm and the fuel ratio difference on Fleet 1 was 0,01 liter/bcm, Fleet 2 was 0,04 liter/tons, Fleet 3 was 0,02 liter/bcm and Fleet 4 was 0,01 liter/bcm. The factors affecting the production loose opportunity from the tool working hour was breakdown, slippery, rain and wait other unit. The total cost spent by the company for the overall fuel consumption was Rp 428.989.792,00 while the overall loss was Rp 45.989.837,74 in March.